Traffic characteristics of car parks in NTU campus - Lim, Cher Xin Yi. (2010)
Although there have been several parking studies done in Singapore, there is no record of such studies that are done for the NTU campus. This report titled: “Traffic characteristics of car parks in NTU campus” summarizes the parking pattern of car parks in the NTU campus. It covers how the student, along with her partner, collaborates with the Office of Facilities Planning and Management (OFPM) to get the necessary data for this report. Furthermore, they have to come up with methods to breakdown each component of the data and put them to good use during analysis. A total of 14 car parks were selected for this parking study and the objectives of this study are to find out the reasons why some car parks are more utilized than the others and also the relationship between the utilization of car parks with the population of staff and students in NTU. Furthermore, the reasons for illegal parking would have to be found out. The results of the analysis of all the car park data suggested that there are a few components as to why some car parks are more utilized that the others. One of the main reasons is whether the car park is a fee charging car park or a free one. It is understandable and is human nature that people would want to park for free than for a fee. Hence car parks like car park A and car park B (fee charging) would not be fully utilized (utilization less than 100%) when compared to free car parks like car parks C, D and E (utilization greater than 100%). But other than monetary reason, location also plays an important part when car users choose a car park. Being able to reach their destinations with ease and convenience is one of the reasons why people choose to drive hence, when choosing a car park, it’s location must be near to where car users want to go. Therefore, car parks at a good location would be more utilized. Furthermore, the result of analysis also tells us that highly utilized car parks are usually located at places where there are more staff and students. With the population of staff and students increases, the number of car users also increases, therefore accounting for some of the car parks being more utilized. This is evident when comparing car parks from the North Spine of the campus with those from the South Spine. North Spine, comparing to the South Spine, having more Schools, Labs and offices in general will have more staff and students and therefore there will be more car users. Car parks at the North Spine will then be relatively more utilized then those at the South Spine. Constant visits to all selected car parks to see whether there are any illegal parking is needed. From the results, illegal parking can be seen in highly utilized car parks like C, D and E while there is no illegal parking seen in the rest of the underutilized car parks.